2012
DOI: 10.1111/j.1365-2249.2011.04505.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune complexes and late complement proteins trigger activation of Syk tyrosine kinase in human CD4+ T cells

Abstract: SummaryIn systemic lupus erythematosus (SLE), the autoantibodies that form immune complexes (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 58 publications
2
18
0
Order By: Relevance
“…ϩ T-cells in the patient population is also supported by our previous studies where we showed Syk phosphorylation during T-cell activation (38). A role for Syk in the development of T H 1 and T H 17 responses via dendritic cell activation has been also been suggested (49).…”
Section: Icsϩc5b-9 Co-signal Triggers Expression Of Genes Associated supporting
confidence: 69%
See 2 more Smart Citations
“…ϩ T-cells in the patient population is also supported by our previous studies where we showed Syk phosphorylation during T-cell activation (38). A role for Syk in the development of T H 1 and T H 17 responses via dendritic cell activation has been also been suggested (49).…”
Section: Icsϩc5b-9 Co-signal Triggers Expression Of Genes Associated supporting
confidence: 69%
“…ϩ T-cells that express Fc␥RIIIa, ICs ligation triggers FcR␥ chain phosphorylation, which then co-localizes and signal via Syk (38,53). Although C5b-9 is essential to trigger MR clustering, ICs engage Fc␥RIIIa and trigger Syk activation (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CD4 ϩ T-cells, engagement of the FcRs by ICs led to the phosphorylation of FcR-␥ chain, which co-localized with phosphorylated Syk kinase (43). In the present study, we show activation induced expression of Fc␥RIIIa in a subset of activated CD4 ϩ T-cells that upon ligation from ICs led to the development of a cell phenotype that produced high amounts of IFN-␥ and expressed T-bet.…”
Section: Discussionmentioning
confidence: 55%
“…10). Increased IC binding was also observed directly in the CD4 ϩ population in SLE patients (43). The IC binding and staining with receptor specific antibodies demonstrated IC co-localization with the receptors (Fig.…”
Section: Discussionmentioning
confidence: 84%